Promoting higher-order thinking skills and learning motivation through the teams games tournaments learning model in physics education: A Rasch model analysis - Aviyanti, Lina; Gani, Amalia Weka; Febriyanti, Tanti; Ribie, Salma; Nawas, Abu (Indonesian Journal of Science and Mathematics Education, 2024)
This study aims to analyze the impact of implementing the Teams Games Tournaments (TGT) learning model on students' Higher-order Thinking Skills (HOTS) and learning motivation in the context of Global Warming. The research employed a quantitative approach, involving 44 eleventh-grade high school students as participants. Data analysis using the stacking test indicated an average logit increase of 1.40 for HOTS and 1.98 for learning motivation. The effect size analysis revealed a large category (1.63) for HOTS and a medium category (0.59) for learning motivation. Additionally, the implementation of the TGT model achieved an average score of 90% in learning quality assessments, accompanied by highly positive student responses. These findings indicate that the TGT learning model is effective in enhancing students' HOTS and learning motivation, particularly for complex physics topics such as Global Warming. The implications of this study suggest that the TGT model can serve as an innovative pedagogical strategy to foster a dynamic learning environment, support better academic achievement, and increase students' enthusiasm for learning.